PENGARUH KOMBINASI EKSTRAK TERPURIFIKASI HERBA SAMBILOTO (Andrographis paniculata (Burm.f.) Nees) DAN HERBA PEGAGAN (Centella asiatica (L.) Urban) TERHADAP TRANSLOKASI PROTEIN GLUT-4 PADA TIKUS DIABETES MELLITUS TIPE 2 RESISTEN INSULIN - Novena Yety Lindawati; Agung Endro Nugroho; Suwijiyo Pramono (Faculty of Pharmacy, Universitas Gadjah Mada, 2014)
Sambiloto herb (Andrographis paniculata (Burm. f.) Nees.) and pegagan herb (Centella asiatica (L.) Urban) are excellent medicinal plants which are being developed as traditional for antidiabetic. The research aims to see the effect of combination from purified extract of sambiloto herb and pegagan herb of translocation of GLUT-4 protein in model type 2 diabetes mellitus rats-insulin resistance compared with the use of each purified extract. Test preparations were divided into 8 groups include three from combination purified extract of sambiloto herb and pegagan herb: I (912,1: 300), II (651,5: 500), III (390,9: 700) in mg/kg BW, IV (purified extract of sambiloto herb 1303 mg/kg BW), V (purified extract of pegagan herb 1000 mg/kg BW), VI (positive control metformin 45 mg/kg BW), VII (negative control CMC-Na 0.5%) and VIII (normal control). Parameters measured semi quantitative data translocation of GLUT-4 protein in cells muscles of the thigh (soleus muscle) rats using Immunohistochemistry methods. Test animals are of type 2 diabetes mellitus insulin-resistance was induced by fructose (1,8 g/kg BW) and fat-rich food (95% pellet, 5% egg yolks and 5 mL/ 200 g BW lard) for 70 days. Determination of insulin resistance used 3 parameters such as blood glucose levels, lipid levels (triglycerides, LDL, cholesterol, and HDL), and hypoglikemic tests with glibenklamid compared to normal controls animals. Insulin resistance test results using statistical analysis Independent Samples t-Test showed significant differences (p< 0.05) between normal rats with fat-fructose rats at day-50 and -70. This indicate fat-fructose rats indicated type 2 DM insulin resistance. Group of combination I (combination purified extract of sambiloto herb and pegagan herb (912,1: 300 mg/kg BB) showed effect of translocation of GLUT-4 protein was better than each purified extract with significantly p<0.05 with oneway ANOVA.